Incidence of viruses infecting spinach in Greece, highlighting the importance of weeds as reservoir hosts - Fotopoulos, Vasileios; Dovas, Chrysostomos I.; Katis, Nikolaos I. (My University, 2011)
The aim of this survey was to identify viruses infecting spinach (Spinacia oleracea L.) in the most important spinach-producing areas in Greece. A total of 1074 spinach samples were collected from eleven districts belonging to the prefectures of Thessaloniki, Chalkidiki and Imathia in northern Greece, and Evia in central Greece. Samples were tested by ELISA, mechanical inoculation onto indicator plants and immunoelectron microscopy. Beet western yellows virus (BWYV), Cucumber mosaic virus (CMV) and Turnip mosaic virus (TuMV) were identified in 13.5%, 7% and 5.4% of samples, respectively, infected samples being detected in all regions examined. This is the first record of CMV and TuMV infecting spinach in Greece, and the first report of BWYV occurrence in any crop nationwide. Surveys were also conducted to assess the potential reservoir hosts of BWYV, CMV and TuMV in weeds collected from spinach fields. All three viruses were detected among 125 samples tested by ELISA. TuMV prevailed as it occurred in 14.4% of all weed samples
Keywords: TUMV; Virus incidence; Spinach; Weeds; ELISA; CMV; BWYV